2019
DOI: 10.1002/hsr2.137
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of respiratory pathogens among children aged younger than 5 years hospitalized with febrile acute respiratory infections: A prospective hospital‐based observational study in Niamey, Niger

Abstract: Background and Aims:In Niger, acute respiratory infections (ARIs) are the second most common cause of death in children aged younger than 5 years. However, the etiology of ARI is poorly understood in the country. This study aims to describe viral and bacterial infections among children aged younger than 5 years hospitalized with febrile ARI at two hospitals in Niamey, Niger's capital city, and the reported clinical procedures. Methods:We conducted a prospective study among children aged younger than 5 years ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Etiology of 2 or more pathogens was documented in 145 patients (54.7%), and the most detected common co-infection groups were RSV/ S. hemolyticus , adenovirus/ H. infuenzae , and S. hemolyticus / H. influenzae . Our data is consistent with some recent reports on ARIs in Africa, which were validated by RT-PCR multiplex assay [ 33 , 34 ]. Therefore, it is necessary to perform a differential diagnosis between viruses and bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Etiology of 2 or more pathogens was documented in 145 patients (54.7%), and the most detected common co-infection groups were RSV/ S. hemolyticus , adenovirus/ H. infuenzae , and S. hemolyticus / H. influenzae . Our data is consistent with some recent reports on ARIs in Africa, which were validated by RT-PCR multiplex assay [ 33 , 34 ]. Therefore, it is necessary to perform a differential diagnosis between viruses and bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings highlight potential roles for S. aureus, K. pneumoniae, M. tuberculosis, adenovirus, GBS, enterovirus, P. aeruginosa, A. baumannii, and influenza A as important causes of SRI, consistent with previous reports in South Africa, Niger and other African countries between 2010 and 2015 (12,23,24,28,29). The 12% detection rate of M. tuberculosis in our study, the majority of which was detected among older children and adults, is in agreement with a previous report in South Africa of 15% prevalence of the pathogen in patients aged >15 years hospitalized with SRI between 2010 and 2011 (29).…”
Section: Discussionsupporting
confidence: 92%
“…A total of 22 papers from 13 countries have reported data on influenza and other respiratory pathogens including both viruses and bacteria . From these, 13 studies reported data on respiratory pathogens among children < 5 years with SARI 145,146,149,151,153,155,156,161,162,[165][166][167]218 , while 9 studied reported data on respiratory pathogens among other age groups 147,148,150,152,[157][158][159][160]163 . The detection of respiratory virus varied considerably.…”
Section: Influenza and Other Respiratory Pathogensmentioning
confidence: 99%